Impact of the dams on water and plankton quality of the River Ganga (Gangotri to Vindhyachal). Issue 2 (17th December 2020) - Srivastava, Kalpana; Kumar, Vijay; Alam, Absar; Nath Jha, Dharm; Ramrao Thakur, Venkatesh; Gupta, Monika; Kumar, Jeetendra; verma, Hariom; Kumar Mishra, Sandeep; Kumar Verma, Sushil; Srivastav, Saket; Shankar Srivastava, Rama; et al.
Abstract: The river Ganga originates from Gangotri and travels approximate 1, 300 km to Vindhyachal, bypassing through a series of dams. Water quality parameters including temperature, pH, dissolved oxygen, alkalinity, chloride, biological oxygen demand, dissolved organic matter, and nutrients were studied from various centers of the river Ganga from Gangotri to Vindhyachal (24 centers). Specific conductivity increased gradually from Maneri above barrage area and reached maximum at Kanpur as the river receives industrial and domestic effluents near Kanpur. Allahabad, Haridwar, and Vindhyachal sampling points were found to be affected by anthropogenic influences. A chloride as well as Myxophyceae were maximum at Kanpur, which indicated that maximum organic pollution at Kanpur plankton population and composition were much more affected by temperature and nutrients than by the construction of dams. However, the pattern of release of water affected the accumulation of nutrients in surface water, which impacted the quality of planktonic fauna and flora. The upper stretch was dominated by diatoms and the middle stretch by green and blue‐green algae as the accumulation of nutrients exhibited eutrophic conditions. Near the source, diatoms like Eunotia, Achanthes, Cymbella, Diatoma, Tabellaria were found to be dominant but as river moves toward downstream, species of Synedra, Melosira, Nitzchia, and Cyclotella became abundant. The study revealed how water quality deteriorated by the construction of each dam. Therefore, when making policy for a dam on any river it is important to maintain at least one stream of the original water flow. The whole river should not be blocked at any point/place or at least 50% of original water should flow continuously to sustain the biodiversity and quality of water, otherwise after traveling a few kilometers through dams, a river will lose its originality. 摘要: 恒河发源于Gangotri，穿越近1300公里到Vindhyachal，途中经过一系列水坝。本文研究了从Gangotri到Vindhyachal的恒河流域内24个中心地区的水质参数，例如温度、pH、溶解氧、碱度、氯化物、生物氧需求、溶解有机物、养分等。电导率从Maner镇水坝区上游逐渐增加，到Kanpur市达到最高值，因为工业污水和家庭废水进入Kanpur附近的水流。此外，Allahabad、 Haridwar 和Vindhyachal中心地区发现存在人类影响。Kanpur地区的氯化物和蓝藻含量最高，这表明Kanpur的有机污染最严重。建造水坝对水质产生了轻微影响，或者水坝区上下游水质参数的较大差异无法被记录，但可以观测到的是，水坝区上游的绿藻含量更高，而下游硅藻含量更高。比起建造水坝产生的影响，浮游生物数量与组成更受温度和养分的影响。然而，水坝的放水模式会影响表面水养分的堆积，这些养分此前又影响浮游生物的质量。上游主要存在硅藻，中游主要存在蓝绿藻，因为养分堆积形成富营养化环境。在近恒河源头地区，Eunotia、Achanthes、Cymbella、Diatoma、Tabellaria等硅藻占多数，但当水流流往下游时，Synedra、Melosira、Nitzchia 和Cyclotella等藻类变得更为充足。 Resumen: El río Ganges se origina en Gangotri y recorre aproximadamente 1300 km hasta Vindhyachal, sin pasar por una serie de presas. Se estudiaron parámetros de calidad del agua como temperatura, pH, oxígeno disuelto, alcalinidad, cloruro, demanda biológica de oxígeno, materia orgánica disuelta, nutrientes, etc. de los diversos centros del río Ganges desde Gangotri hasta Vindhyachal (24 centros). La conductividad específica aumentó gradualmente desde Maneri por encima del área de la presa y alcanzó su máximo en Kanpur cuando el río recibe efluentes industriales y domésticos cerca de Kanpur. Además, se descubrió que los centros de Allahabad, Haridwar y Vindhyachal estaban afectados por influencias antropogénicas. Los cloruros, así como Myxophyceae, fueron máximos en Kanpur, lo que indicó la máxima contaminación orgánica en Kanpur. La construcción de la presa afectó la calidad del agua leve o mucha diferencia en los parámetros de calidad del agua de las áreas por encima y por debajo de la presa no se pudo registrar, pero se puede observar que en las áreas por encima de la presa, la contribución de clorofíceas fue mayor, mientras que en las áreas por debajo de la presa la contribución de Bacillariophyceae fue mayor. La población y la composición del plancton se vieron muy afectadas por la temperatura y los nutrientes en comparación con la construcción de represas. Sin embargo, el patrón de liberación de agua afectó la acumulación de nutrientes en el agua superficial, lo que había impactado la calidad de la fauna y flora planctónicas. El tramo superior estuvo dominado por diatomeas y el tramo medio por algas verdes y azul verdosas debido a que la acumulación de nutrientes exhibió condiciones eutróficas. Cerca de la fuente, se encontró que las diatomeas como Eunotia, Achanthes, Cymbella, Diatoma, Tabellaria eran dominantes, pero a medida que el río avanza hacia aguas abajo, las especies de Synedra, Melosira, Nitzchia y Cyclotella se volvieron abundantes.